The role of teachers in improving students' digital literacy in the 21st century learning era - Fanni Fanni Tamara; Jaja Jaja; Jimat Susilo (Jurnal Bebasan, 2025)
This research aims to examine the role of teachers in improving students' digital literacy in the 21st-century learning era through the library research method. The results of the study show that teachers play an important role as facilitators, motivators, and supervisors in developing students' ability to access, evaluate, and use digital information critically and ethically. Strategies such as blended learning and the use of digital media have proven effective in increasing student engagement. However, challenges such as limited infrastructure and a lack of teacher training remain major obstacles. This study recommends the need for cross-sectoral collaboration to support the strengthening of digital literacy through systematic integration in the educational curriculum.